A high-peeling, high-temperature-resistant polyacrylate pressure-sensitive adhesive and its preparation method and application
By using the crosslinking structure of star-shaped fluorine-containing block copolymer and hyperbranched polysiloxane in polyacrylate pressure-sensitive adhesive, the heat resistance and peel strength of polyacrylate pressure-sensitive adhesive in high temperature environments is solved. , achieving efficient improvement of film performance and extended service life.
Patent Information
- Application Number
- CN202410286792.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-13
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-03-13
AI Technical Summary
Polyacrylate pressure-sensitive adhesives are prone to cause problems such as degumming and edge curling in long-term high-temperature environments. In the prior art, when the fluoro-silicon distribution is added to add silicone monomers and other copolymers, the fluoro-silicon distribution becomes uneven and the viscosity becomes worse, and the peel strength is low. It is difficult to have both heat resistance, high peel strength and low residual glue performance.
Using star-shaped fluorine-containing block copolymer and hyperbranched polysiloxane as heat-resistant components, the distribution uniformity and peel strength of fluorine silicon are improved through the crosslinking network structure, and combining polyacrylate to form a stable crosslinking structure to enhance Cohesive and heat resistance of colloids.
The high heat resistance, high peel strength and low residual glue performance of polyacrylate pressure-sensitive adhesive are achieved, ensuring stable adhesion and easy replacement under high temperature environments and extending service life.
Smart Images

Figure BDA0004739376730000121
Abstract
Description
Technical Field
[0001] The present application relates to the field of pressure-sensitive adhesives, and more specifically, to a high-peeling, high-temperature-resistant polyacrylate pressure-sensitive adhesive and a preparation method and application thereof. Background Art
[0002] Pressure sensitive adhesive is a pressure-sensitive adhesive that can achieve adhesion to the substrate through slight pressure. Polyacrylate pressure sensitive adhesive is the most widely used type of pressure sensitive adhesive. It has excellent weather resistance, acid and alkali resistance, good transparency, better uniformity than organic silicone, and is not easy to migrate. However, the heat resistance of polyacrylate often cannot meet the use requirements. Long-term use in high temperature environments will lead to degumming, warping, etc.
[0003] It is a common application to cover a layer of film on the substrate by using a pressure-sensitive adhesive as an adhesive layer to play a certain protective role. Films used in long-term outdoor environments or special high-temperature environments, such as in the automotive field, are usually covered with a layer of glass window film on their surface in order to protect glass windows and prevent the insecurity caused by glass shattering. It is compounded on thin film materials such as PET through pressure-sensitive adhesive and adhered to the surface of the glass window by pressure. Some electronic industries have higher requirements for the high temperature resistance of pressure-sensitive adhesives. Therefore, it is expected that polyacrylate pressure-sensitive adhesives have better heat resistance, high peel strength, low residual adhesive after peeling, etc., in order to cope with the high-temperature use environment and simplify the subsequent processing process. In the prior art, polyacrylates are usually prepared by copolymerization by adding silicone monomers, fluorine monomers, etc. to improve the heat resistance of pressure-sensitive adhesives, but the entanglement of acrylic acid chains and the randomness of copolymerization make fluorine silicon unevenly distributed in the system, thereby affecting its heat resistance effect, and the introduction of too much fluorine silicon monomers is easy to lead to poor adhesion, low peel strength, and residual adhesive after peeling, which is not conducive to the long-term adhesion of pressure-sensitive adhesives and increases the difficulty of replacement process. Therefore, how to make the pressure-sensitive adhesive have higher heat resistance, high peel strength and low residual adhesive is a problem that needs to be solved urgently. Summary of the invention
[0004] In order to solve the problem that polyacrylate pressure-sensitive adhesive has heat resistance, high peel strength and low residual adhesive, the present application provides a high-peeling and high-temperature-resistant polyacrylate pressure-sensitive adhesive and a preparation method and application thereof.
[0005] In a first aspect, the present application provides a high-peeling, high-temperature-resistant polyacrylate pressure-sensitive adhesive, comprising the following components in parts by weight:
[0006] 100 parts of polyacrylate rubber,
[0007] 10-25 parts of heat-resistant components,
[0008] 0-2 parts of additives,
[0009] 40-70 parts of solvent;
[0010] The heat-resistant component is: star-shaped fluorine-containing block copolymer and / or hyperbranched polysiloxane.
[0011] Through the above technical scheme, polyacrylate adhesive can be obtained by polymerizing conventional acrylic monomers. Polyacrylate as the main body of the adhesive provides excellent weather resistance and transparency of the pressure-sensitive adhesive. When the inventor hopes to improve the heat resistance of polyacrylate pressure-sensitive adhesive, in addition to copolymerization through fluorosilicon monomers, he tends to find a better way to introduce fluorosilicon into the pressure-sensitive adhesive. By adding star-shaped fluorinated block copolymers, the fluorine atoms can be better distributed in the pressure-sensitive adhesive based on the structure of multiple branches extending from the same initiator end of the star-shaped polymer. The fluorinated segments in the block copolymer improve the heat resistance of the pressure-sensitive adhesive, and the hydroxyl-containing segments in the block copolymer improve the peel strength, which can further react with polyacrylate to form a cross-linked network structure and increase cohesion. At the same time, the distribution of fluorine atoms in the adhesive is stabilized, and better heat resistance can be achieved by adding a small amount of them. The inventors also found through experiments that adding hyperbranched polysiloxane as a heat-resistant component can also improve the heat resistance of the pressure-sensitive adhesive. Hyperbranched polysiloxane itself contains silicon-oxygen bonds and has excellent heat resistance. The large number of branched structures of hyperbranched polysiloxane can make the silicon-oxygen bonds stably distributed in the system, which has better heat resistance than conventional linear polysiloxane. At the same time, hyperbranched polysiloxane has a large number of active groups, which can further improve the peel strength of the pressure-sensitive adhesive after cross-linking. Surprisingly, by mixing hyperbranched polysiloxane and star-shaped fluorinated block copolymers, the heat resistance is better, the peel strength is high, and the residual adhesive is less. The inventors believe that this may be because the hyperbranched siloxane contains a large number of active groups, which can improve the peel strength of the pressure-sensitive adhesive and can also cross-link with polyacrylates. The large number of active groups in the hyperbranched siloxane can also cross-link with the hydroxyl segments in the star-shaped fluorinated block copolymer. Combined with polyacrylate, the fluorine and silicon are evenly distributed in the overall pressure-sensitive adhesive. The hyperbranched polysiloxane is combined with the hydroxyl segments of the fluorinated block copolymer and cross-linked with the polyacrylate, so that the pressure-sensitive adhesive liquid contains dispersed and stable heat-resistant components. The heat resistance of the polyacrylate is good by adding a small amount. At the same time, through the multiple cross-linking of the special structure of the two heat-resistant components, the influence of fluorine and silicon on the viscosity of the pressure-sensitive adhesive is reduced. The obtained pressure-sensitive adhesive can also have excellent peel strength and less residual adhesive.
[0012] In a specific embodiment, the heat-resistant component is a mixture of a star-shaped fluorinated block copolymer and a hyperbranched polysiloxane in a weight ratio of (2-4):1.
[0013] The inventors have found through experiments that the pressure-sensitive adhesive has the best performance in all aspects by the weight ratio range of the star-shaped fluorinated block copolymer and the hyperbranched polysiloxane in the above scheme. This may be because the star-shaped fluorinated block copolymer and the hyperbranched polysiloxane in the above weight ratio range are mixed, the hyperbranched polysiloxane and the hydroxyl-containing segments in the block copolymer are properly cross-linked, and can achieve a good cross-linking effect with the polyacrylate, so that the fluorine and silicon are more evenly distributed, the distribution stability is better, and the fluorine and silicon content in the pressure-sensitive adhesive is appropriate, and the heat resistance effect is better.
[0014] In a specific embodiment, the preparation steps of the star-shaped fluorinated block copolymer include: dissolving 40-60 parts of fluorinated monomer in 100-200 parts of xylene, adding 1-2 parts of initiator, 1-2 parts of catalyst, and 2-4 parts of ligand under an inert gas atmosphere, mixing evenly, heating to 80-90°C for reaction for 15-20h, dissolving in tetrahydrofuran, precipitating in methanol, filtering, washing, and drying to obtain a white solid after the reaction is completed; dissolving 40-60 parts of hydroxyl-containing monomer in 100-200 parts of xylene, adding 1-4 parts of the above-prepared white solid, 1-2 parts of catalyst, and 2-4 parts of ligand under an inert gas atmosphere, mixing evenly, heating to 80-90°C for reaction for 15-20h, dissolving in tetrahydrofuran, precipitating in methanol, filtering, washing, and drying to obtain a star-shaped fluorinated block copolymer.
[0015] Preferably, the fluorine-containing monomer is trifluoroethyl methacrylate; the hydroxyl-containing monomer is hydroxyethyl acrylate; the initiator is octachloropropylsilsesquioxane; the catalyst is cuprous chloride; the ligand is pentamethyldiethylenetriamine; and the inert gas is nitrogen.
[0016] Star-shaped block copolymers can be prepared by using octachloropropyl silsesquioxane as an initiator. The silicon-oxygen bonds of octachloropropyl silsesquioxane itself can improve the heat resistance of the copolymer, and its eight chlorine atoms can be used as an initiator of atom transfer radicals, thereby initiating polymerization of monomers with octachloropropyl silsesquioxane as the center to obtain a star-shaped polymer structure with eight branches. The inventor obtained fluorine-containing and hydroxyl-containing block carbon chains by grafting fluorine-containing monomers and hydroxyl-containing monomers. The reaction of hyperbranched polysiloxane and hydroxyl segments can make the distribution of fluorine and silicon in the system more stable and uniform, and improve the heat resistance of the pressure-sensitive adhesive when the addition amount is very small. The specific synthesis is a conventional atom transfer radical system.
[0017] In a specific embodiment, the raw materials for preparing the polyacrylate rubber include: soft monomers, hard monomers, functional monomers, initiators, and diluents.
[0018] The inventors selected conventional soft monomers, hard monomers, functional monomers, initiators, and diluents as raw materials for preparing polyacrylate colloids. Among them, functional monomers are necessary for the high peeling, low residual glue performance and heat resistance of the system. Preferably, the soft monomer includes one or more of butyl acrylate, isobutyl acrylate, and isooctyl acrylate; the hard monomer includes one or more of methyl acrylate, methyl methacrylate, and vinyl acetate; the functional monomer includes one or more of acrylic acid, hydroxyethyl acrylate, and hydroxyethyl methacrylate; the initiator includes one or more of azobisisobutyronitrile and benzoyl peroxide; the diluent includes one or more of ethyl acetate, toluene, and butyl acetate. The polyacrylate colloid prepared by the above raw materials can have a greater improvement in performance by adding heat-resistant components.
[0019] In a specific embodiment, the auxiliary agent includes: one or more of a cross-linking agent, an ultraviolet light absorber, and a leveling agent.
[0020] The solvent is one or more of ethyl acetate, toluene and butyl acetate.
[0021] There is no restriction on the addition of auxiliary agents and solvents in the present application. The auxiliary agent is preferably 0.2-2 parts, and a small amount of crosslinking agent, ultraviolet light absorber, and leveling agent can be added based on demand to improve the performance of the pressure-sensitive adhesive, and the choice of solvent is based on the ability to dissolve the components, and any suitable solvent can be used in the pressure-sensitive adhesive of the present application.
[0022] In a second aspect, the present application provides a method for preparing a high-peelable and high-temperature-resistant polyacrylate pressure-sensitive adhesive. The method comprises the following steps: adding polyacrylate adhesive to a solvent according to a ratio and stirring evenly, then adding a heat-resistant component and an auxiliary agent and mixing evenly to obtain a high-peelable and high-temperature-resistant polyacrylate pressure-sensitive adhesive.
[0023] In the third aspect, the present application provides an application of a high-peeling, high-temperature-resistant polyacrylate pressure-sensitive adhesive in a high-temperature-resistant film. The pressure-sensitive adhesive of the present application is used in long-term high-temperature outdoor or special environments, such as glass window films. The good flexibility of the hyperbranched polysiloxane can make the pressure-sensitive adhesive film composite material more fit the shape of the car body during construction, and can also achieve a certain effect of resisting the impact of wind, sand and stones. When the glass explodes, the higher peel strength and cohesion can enable the pressure-sensitive adhesive to prevent the splash of glass fragments and avoid safety hazards.
[0024] In summary, this application has at least the following beneficial effects:
[0025] 1. This application adds star-shaped fluorinated block copolymers to achieve better distribution of fluorine atoms in the pressure-sensitive adhesive based on the star-shaped molecular structure, with good heat resistance. The hydroxyl-containing segments in the block copolymers improve the peel strength and can further react with polyacrylate to form a cross-linked network structure, which stabilizes the distribution of fluorine atoms in the adhesive. A small amount of addition achieves better heat resistance, and the cross-linked structure also improves the cohesion of the pressure-sensitive adhesive. A small amount of hyperbranched polysiloxane is used as a heat-resistant component and mixed with star-shaped fluorinated block copolymers, which has better heat resistance, high peel strength, and less residual adhesive. Combined with polyacrylate, the overall pressure-sensitive adhesive has a uniform distribution of fluorine and silicon, good heat resistance, and excellent peel strength and less residual adhesive.
[0026] 2. In the present application, the heat-resistant component is preferably a mixture of a star-shaped fluorinated block copolymer and a hyperbranched polysiloxane in a weight ratio of (2-4):1, so that the cross-linking effect of the polyacrylate, star-shaped fluorinated block copolymer and hyperbranched polysiloxane in the pressure-sensitive adhesive is appropriate, thereby further optimizing the heat resistance, high peel strength and low residual adhesive of the pressure-sensitive adhesive.
[0027] 3. The present application uses octachloropropyl silsesquioxane as an initiator and prepares a block copolymer by atom transfer radical polymerization, so that the crosslinking of octachloropropyl silsesquioxane, fluorine-containing segments, hydroxyl-containing segments and hyperbranched polysiloxane can jointly exert a heat-resistant effect, achieving better heat-resistant effect with a small amount of addition, while improving the peel strength and reducing the residual adhesive, thereby ensuring the adhesion of the pressure-sensitive adhesive and extending the service life. DETAILED DESCRIPTION
[0028] The present application is further described in detail below in conjunction with the examples. The hydroxyl-terminated polydimethylsiloxane used in the examples and preparation examples was purchased from Macklin P856624; octachloropropylsilsesquioxane was purchased from Aladdin O140428; other experimental reagents in the preparation examples or examples, unless otherwise specified, are conventional commercial brands or obtained through conventional preparation processes.
[0029] Any conventional polymerization system that can be used to prepare polyacrylate can be used to prepare the polyacrylate of the present application. In the present application, the following process is used:
[0030] Add soft monomer, hard monomer and functional monomer to 60wt% diluent and stir evenly, heat to 75°C under nitrogen protection, add 50wt% initiator and 20wt% diluent mixture, heat to 85°C and react for 1h, then add the other half 50wt% initiator and 20wt% diluent mixture, keep warm and react for 5h, then cool down to obtain polyacrylate rubber.
[0031] Preparation Example 1:
[0032] Add 60g of butyl acrylate, 20g of methyl methacrylate, 10g of methyl acrylate, 10g of acrylic acid and 10g of hydroxyethyl acrylate into 60g of ethyl acetate and stir evenly. Heat the reactor to 75°C under nitrogen protection. Mix 0.2g of initiator azobisisobutyronitrile and 20g of ethyl acetate evenly, add them into the reactor, heat to 85°C and react for 1h. Then, mix 0.2g of azobisisobutyronitrile and 20g of ethyl acetate evenly and add them. Keep the temperature for reaction for 5h and then cool down to obtain the polyacrylate rubber.
[0033] Any preparation system that can be used to prepare hyperbranched polysiloxane containing active groups can be used to prepare the hyperbranched polysiloxane of the present application. In the present application, the hyperbranched polysiloxane is prepared by conventional hydrolysis method.
[0034] Preparation Example 2:
[0035] Add 248g of r-methacryloxypropyltrimethoxysilane into the reactor, add 27g of distilled water and 1.6g of concentrated hydrochloric acid dropwise while stirring, stir at room temperature for 40 minutes, heat to 55°C, keep warm for reaction for 3 hours, then cool to room temperature, add 4g of sodium bicarbonate and stir for 30 minutes, filter, heat to 50°C, and polymerize under reduced pressure for 2 hours to obtain a hyperbranched polysiloxane containing hydroxyl active groups.
[0036] Preparation of star-shaped fluorinated block copolymers of the present application:
[0037] Dissolve 40-60 parts of fluorine-containing monomer in 100-200 parts of xylene, add 1-2 parts of initiator, 1-2 parts of catalyst and 2-4 parts of ligand under inert gas atmosphere, mix evenly, heat to 80-90°C for reaction for 15-20h, dissolve in tetrahydrofuran, precipitate with methanol, filter, wash and dry to obtain a white solid; dissolve 40-60 parts of hydroxyl-containing monomer in 100-200 parts of xylene, add 1-4 parts of prepared white solid, 1-2 parts of catalyst and 2-4 parts of ligand under inert gas atmosphere, mix evenly, heat to 80-90°C for reaction for 15-20h, dissolve in tetrahydrofuran, precipitate with methanol, filter, wash and dry to obtain a star-shaped fluorine-containing block copolymer.
[0038] Preparation Example 3:
[0039] Dissolve 50g of trifluoroethyl methacrylate in 150g of xylene, replace with nitrogen, add 1.5g of initiator octachloropropyl silsesquioxane, 1g of catalyst cuprous chloride, and 2g of ligand pentamethyldiethylenetriamine, mix and stir, heat to 90°C and react for 20 hours, add tetrahydrofuran to dissolve after the reaction, add a large amount of methanol to precipitate to obtain flocs, filter after precipitation, wash with deionized water 1-3 times, and dry to obtain a white solid, dissolve 50g of hydroxyethyl acrylate in 150g of xylene, replace with nitrogen, add 3g of the prepared white solid, 1g of catalyst cuprous chloride, and 2g of ligand pentamethyldiethylenetriamine to mix and stir, heat to 85°C and react for 20 hours, add tetrahydrofuran to dissolve after the reaction, add a large amount of methanol to precipitate to obtain flocs, filter after precipitation, wash with deionized water 3 times, and dry to obtain a star-shaped fluorinated block copolymer.
[0040] Preparation Example 4:
[0041] 45 g of trifluoroethyl methacrylate was dissolved in 150 g of xylene, and nitrogen was introduced for replacement. 1.2 g of initiator octachloropropyl silsesquioxane, 1 g of catalyst cuprous chloride, and 2 g of ligand pentamethyldiethylenetriamine were added and mixed and stirred. The temperature was raised to 90° C. and reacted for 20 hours. After the reaction was completed, tetrahydrofuran was added to dissolve, and a large amount of methanol was added to precipitate to obtain flocs. After precipitation, it was filtered, washed with deionized water 1-3 times, and dried to obtain a white solid. 50 g of hydroxyethyl acrylate was dissolved in 150 g of xylene, and nitrogen was introduced for replacement. 3.2 g of the prepared white solid, 1 g of catalyst cuprous chloride, and 2 g of ligand pentamethyldiethylenetriamine were added and mixed and stirred. The temperature was raised to 85° C. and reacted for 20 hours. After the reaction was completed, tetrahydrofuran was added to dissolve, and a large amount of methanol was added to precipitate to obtain flocs. After precipitation, it was filtered, washed with deionized water 3 times, and dried to obtain a star-shaped fluorinated block copolymer.
[0042] Preparation Example 5:
[0043] Preparation of star-shaped fluorinated homopolymer: 50 g of trifluoroethyl methacrylate was dissolved in 150 g of xylene, and nitrogen was introduced for replacement. 1.5 g of initiator octachloropropylsilsesquioxane, 1 g of catalyst cuprous chloride, and 2 g of ligand pentamethyldiethylenetriamine were added and mixed and stirred. The temperature was raised to 90° C. and reacted for 20 hours. After the reaction was completed, tetrahydrofuran was added to dissolve, and a large amount of methanol was added to precipitate to obtain flocs. After precipitation, the flocs were filtered, washed with deionized water 1-3 times, and dried to obtain a star-shaped fluorinated acrylic homopolymer.
[0044] Example 1
[0045] 0.4 g of cross-linking agent hexamethylene diisocyanate was added to 60 g of ethyl acetate solvent and stirred evenly, then 100 g of the polyacrylate base material prepared in Preparation Example 1 was added and continued to be stirred evenly, and 16 g of the star-shaped fluorinated block copolymer prepared in Preparation Example 3 was added and stirred to obtain a polyacrylate pressure-sensitive adhesive.
[0046] Example 2
[0047] 0.2 g of cross-linking agent hexamethylene diisocyanate was added to 65 g of ethyl acetate solvent and stirred evenly, then 100 g of the polyacrylate base material prepared in Preparation Example 1 was added and continued to be stirred evenly, and 20 g of the star-shaped fluorinated block copolymer prepared in Preparation Example 3 was added and stirred to obtain a polyacrylate pressure-sensitive adhesive.
[0048] Example 3
[0049] 0.4 g of cross-linking agent hexamethylene diisocyanate was added to 60 g of ethyl acetate solvent and stirred evenly, then 100 g of the polyacrylate base material prepared in Preparation Example 1 was added and continued to be stirred evenly, and 16 g of the star-shaped fluorinated block copolymer prepared in Preparation Example 4 was added and stirred to obtain a polyacrylate pressure-sensitive adhesive.
[0050] Example 4
[0051] 0.4 g of cross-linking agent hexamethylene diisocyanate was added to 60 g of ethyl acetate solvent and stirred evenly, then 100 g of the polyacrylate base material prepared in Preparation Example 1 was added and continued to be stirred evenly, and 16 g of the hyperbranched polysiloxane prepared in Preparation Example 2 was added and stirred to obtain a polyacrylate pressure-sensitive adhesive.
[0052] Example 5
[0053] 0.4 g of crosslinking agent hexamethylene diisocyanate was added to 60 g of ethyl acetate solvent and stirred evenly, then 100 g of the polyacrylate base material prepared in Preparation Example 1 was added and continued to be stirred evenly, 8 g of the star-shaped fluorinated block copolymer prepared in Preparation Example 3 and 8 g of the hyperbranched polysiloxane prepared in Preparation Example 2 were added and stirred to obtain a polyacrylate pressure-sensitive adhesive.
[0054] Example 6
[0055] 0.4 g of cross-linking agent hexamethylene diisocyanate was added to 60 g of ethyl acetate solvent and stirred evenly, then 100 g of the polyacrylate base material prepared in Preparation Example 1 was added and continued to be stirred evenly, 12 g of the star-shaped fluorinated block copolymer prepared in Preparation Example 3 and 4 g of the hyperbranched polysiloxane prepared in Preparation Example 2 were added and stirred to obtain a polyacrylate pressure-sensitive adhesive.
[0056] Example 7
[0057] 0.4 g of cross-linking agent hexamethylene diisocyanate was added to 60 g of ethyl acetate solvent and stirred evenly, then 100 g of the polyacrylate base material prepared in Preparation Example 1 was added and continued to be stirred evenly, 13 g of the star-shaped fluorinated block copolymer prepared in Preparation Example 3 and 3 g of the hyperbranched polysiloxane prepared in Preparation Example 2 were added and stirred to obtain a polyacrylate pressure-sensitive adhesive.
[0058] Example 8
[0059] 0.4 g of the crosslinking agent hexamethylene diisocyanate was added to 60 g of ethyl acetate solvent and stirred evenly, then 100 g of the polyacrylate base material prepared in Preparation Example 1 was added and continued to be stirred evenly, 4 g of the star-shaped fluorinated acrylic homopolymer prepared in Preparation Example 5 and 12 g of the hyperbranched polysiloxane prepared in Preparation Example 2 were added and stirred to obtain a polyacrylate pressure-sensitive adhesive.
[0060] Example 9
[0061] 0.4 g of crosslinking agent hexamethylene diisocyanate was added to 60 g of ethyl acetate solvent and stirred evenly, then 100 g of the polyacrylate base material prepared in Preparation Example 1 was added and continued to be stirred evenly, 12 g of the star-shaped fluorinated block copolymer prepared in Preparation Example 3 and 4 g of hydroxyl-terminated polydimethylsiloxane were added and stirred to obtain a polyacrylate pressure-sensitive adhesive.
[0062] Comparative Example 1
[0063] 0.4 g of hexamethylene diisocyanate, a cross-linking agent, was added to 60 g of ethyl acetate solvent and stirred evenly, and then 100 g of the polyacrylate base material prepared in Preparation Example 1 was added and stirred evenly to obtain a polyacrylate pressure-sensitive adhesive.
[0064] Comparative Example 2
[0065] 0.4 g of crosslinking agent hexamethylene diisocyanate was added to 60 g of ethyl acetate solvent and stirred evenly, then 100 g of the polyacrylate base material prepared in Preparation Example 1 was added and continued to be stirred evenly, and 16 g of the star-shaped fluorinated acrylic homopolymer prepared in Preparation Example 5 was added and stirred to obtain a polyacrylate pressure-sensitive adhesive.
[0066] Comparative Example 3
[0067] 0.4 g of cross-linking agent hexamethylene diisocyanate was added to 60 g of ethyl acetate solvent and stirred evenly, then 100 g of the polyacrylate base material prepared in Preparation Example 1 was added and continued to be stirred evenly, and 16 g of hydroxyl-terminated polydimethylsiloxane was added and stirred to obtain a polyacrylate pressure-sensitive adhesive.
[0068] Performance testing:
[0069] 1. Peel strength test: The samples of Examples 1-9 and Comparative Examples 1-3 were coated on a substrate to prepare a PET pressure-sensitive tape, and the peel strength of the pressure-sensitive tape on a stainless steel plate was tested according to GB / T2792-2014.
[0070] 2. High temperature resistance test: The stainless steel plates adhered with the PET pressure-sensitive tapes of the samples of Examples 1-9 and Comparative Examples 1-3 were placed in an oven at 180°C and baked for 5 hours, and then subjected to a peel strength test to observe and record the residual adhesive.
[0071] The performance test results of the embodiments and comparative examples are shown in Table 1:
[0072]
[0073] In combination with Examples 1-3 of the present application and Comparative Example 1, it can be seen that by adding a heat-resistant component, the peel strength of the polyacrylate pressure-sensitive adhesive of the present application is not only improved, but the adhesive film after high-temperature treatment still maintains excellent peel strength, reflecting excellent high-temperature resistance, and only a small amount of residual adhesive is left after peeling. This may be due to the addition of star-shaped fluorinated block copolymers or hyperbranched polysiloxanes, which, by leveraging the advantages of the polymer structure, achieve a more uniform distribution of silicon oxygen or fluorine, thereby improving the high-temperature resistance of the pressure-sensitive adhesive. At the same time, the active groups in the heat-resistant components and the acrylic ester colloid further enhance crosslinking, thereby enhancing the peel strength of the pressure-sensitive adhesive and reducing residual adhesive.
[0074] It can be seen from the combination of Example 1 and Example 4-7 of the present application that by adding star-shaped fluorinated block copolymer and hyperbranched polysiloxane as heat-resistant components to polyacrylate pressure-sensitive adhesive, the peel strength and heat resistance are improved more than adding star-shaped fluorinated block copolymer or hyperbranched polysiloxane alone. This may be due to the fact that a large number of active groups of hyperbranched siloxane can cross-link with the hydroxyl-containing segments in the star-shaped fluorinated block copolymer, and the combination of polyacrylate makes the fluorine and silicon in the overall pressure-sensitive adhesive evenly distributed, and the stable existence achieved by the cross-linking of active groups in the colloid through the reasonable distribution of fluorinated groups and silicon-oxygen bonds and the cross-linking of active groups in the colloid makes the pressure-sensitive adhesive have good heat resistance, and at the same time enhances the cohesion of the colloid, has high peel strength, and has no residual adhesive phenomenon after peeling at high temperature.
[0075] In addition, the inventors also tested and found that the peel strength and heat resistance of Example 6 are better than those of Examples 5 and 7. This may be due to the mixed use of the star-shaped fluorinated block copolymer and the hyperbranched polysiloxane within the weight ratio range of Example 6, the hyperbranched polysiloxane and the hydroxyl-containing segments in the block copolymer are properly cross-linked, and can achieve good cross-linking with the polyacrylate, making the fluorine-silicon distribution more uniform, the distribution stability better, and the heat resistance better.
[0076] It can be seen from Examples 6, 8 and 9 that when the star-shaped fluorine-containing polymer does not contain active segments, or the polysiloxane is not a hyperbranched polysiloxane, its peel strength and heat resistance are slightly reduced. This may be because the reduction of active groups in the system leads to unstable distribution of fluorine and silicon in the system, and reduced cross-linking of the colloid, resulting in loss of performance. Example 1, Example 4 and Comparative Examples 2-3 further demonstrate the influence of the active group segments of the star-shaped fluorine-containing copolymer and the hyperbranched structural factors of the polysiloxane on the performance.
[0077] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A high-peeling, high-temperature-resistant polyacrylate pressure-sensitive adhesive, characterized in that: It is composed of the following components in parts by weight: 100 parts of polyacrylate rubber, 10-25 parts of heat-resistant components, 0-2 parts of additives, 40-70 parts of solvent; The heat-resistant component is a mixture of a star-shaped fluorinated block copolymer and a hyperbranched polysiloxane in a weight ratio of (2-4):1; The star-shaped fluorinated block copolymer preparation steps include: dissolving 40-60 parts of a fluorinated monomer in 100-200 parts of xylene, adding 1-2 parts of an initiator, 1-2 parts of a catalyst, and 2-4 parts of a ligand in an inert gas atmosphere, mixing evenly, heating to 80-90° C. for reaction for 15-20 hours, dissolving in tetrahydrofuran after the reaction, precipitating in methanol, filtering, washing, and drying to obtain a white solid; dissolving 40-60 parts of a hydroxyl-containing monomer in 100-200 parts of xylene, adding 1-4 parts of a prepared white solid, 1-2 parts of a catalyst, and 2-4 parts of a ligand in an inert gas atmosphere, mixing evenly, heating to 80-90° C. for reaction for 15-20 hours, dissolving in tetrahydrofuran after the reaction, precipitating in methanol, filtering, washing, and drying to obtain a star-shaped fluorinated block copolymer; the fluorinated monomer is trifluoroethyl methacrylate; and the initiator is octachloropropylsilsesquioxane; The solvent is one or more of ethyl acetate, toluene and butyl acetate.
2. The high-peeling, high-temperature-resistant polyacrylate pressure-sensitive adhesive according to claim 1, characterized in that: The hydroxyl-containing monomer is hydroxyethyl acrylate; the catalyst is cuprous chloride; the ligand is pentamethyldiethylenetriamine; and the inert gas is nitrogen.
3. The high-peeling, high-temperature-resistant polyacrylate pressure-sensitive adhesive according to claim 1, characterized in that: The raw materials for preparing the polyacrylate sizing material include: soft monomer, hard monomer, functional monomer, initiator and diluent.
4. The high-peeling, high-temperature-resistant polyacrylate pressure-sensitive adhesive according to claim 3, characterized in that: The soft monomer includes one or more of butyl acrylate, isobutyl acrylate, and isooctyl acrylate; the hard monomer includes one or more of methyl acrylate, methyl methacrylate, and vinyl acetate; the functional monomer includes one or more of acrylic acid, hydroxyethyl acrylate, and hydroxyethyl methacrylate; the initiator includes one or more of azobisisobutyronitrile and benzoyl peroxide; and the diluent includes one or more of ethyl acetate, toluene, and butyl acetate.
5. The high peeling and high temperature resistant polyacrylate pressure sensitive adhesive according to claim 1, characterized in that: The auxiliary agent includes: one or more of a cross-linking agent, an ultraviolet light absorber, and a leveling agent.
6. A method for preparing the high-peeling, high-temperature-resistant polyacrylate pressure-sensitive adhesive according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: adding polyacrylate adhesive into solvent according to a proportion and stirring evenly, then adding heat-resistant components and auxiliary agents and mixing evenly to obtain high-peeling and high-temperature-resistant polyacrylate pressure-sensitive adhesive.
7. Use of the high-peeling, high-temperature-resistant polyacrylate pressure-sensitive adhesive according to any one of claims 1 to 5 in a high-temperature-resistant film.